2011
DOI: 10.1002/chem.201002465
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatisation of o‐Xylene by P450BM3 (CYP102A1)

Abstract: The oxidation of o-xylene by P450(BM3) from Bacillus megaterium yields, in addition to the products formed by microsomal P450s, two metabolites containing an NIH-shifted methyl group, one of which lacks the aromatic character of the substrate. The failure of the epoxide precursor of these two products to rearrange to the more stable 2,7-dimethyloxepin suggests that ring opening is P450-mediated. With m-xylene, the principal metabolite is 2,4-dimethylphenol. The partition between aromatic and benzylic hydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 62 publications
4
71
0
6
Order By: Relevance
“…Previously, it was shown that the residue at position 87 can play a critical role in substrate binding and in the change of the spin state of the haem iron, thereby possibly affecting trends in regioselectivity by P450 BM3 mutants. 31 In terms of aromatic or benzylic hydroxylation of compounds by engineered P450 BM3, hydroxylation of xylenes have been studied and it has been previously shown that the active site architecture and the residue at position 87 can play a role in determining the preference for hydroxylation in line with our experimental observations. 31,32 Moreover, kinetic isotope effects have also been used to delineate the importance of residue at position 87 for aromatic or benzylic hydroxylation.…”
Section: Selective Benzylic Vs Aromatic Hydroxylation Of 1 By Engineesupporting
confidence: 85%
“…Previously, it was shown that the residue at position 87 can play a critical role in substrate binding and in the change of the spin state of the haem iron, thereby possibly affecting trends in regioselectivity by P450 BM3 mutants. 31 In terms of aromatic or benzylic hydroxylation of compounds by engineered P450 BM3, hydroxylation of xylenes have been studied and it has been previously shown that the active site architecture and the residue at position 87 can play a role in determining the preference for hydroxylation in line with our experimental observations. 31,32 Moreover, kinetic isotope effects have also been used to delineate the importance of residue at position 87 for aromatic or benzylic hydroxylation.…”
Section: Selective Benzylic Vs Aromatic Hydroxylation Of 1 By Engineesupporting
confidence: 85%
“…[12a,d, 14] Der Mechanismus der aromatischen Hydroxylierung wurde durch de Visser und Shaik im Detail beschrieben und umfasst die Bildung einer Epoxid-Zwischenstufe, die nach NIH-Verschiebung zum phenolischen Produkt rearomatisiert. [14] 2012 wurde die P450 BM3-Variante M2 (R47S/Y51W/ I401M) in unserer Gruppe für die regioselektive und aromatische Hydroxylierung von p-Xylol entwickelt. [14] 2012 wurde die P450 BM3-Variante M2 (R47S/Y51W/ I401M) in unserer Gruppe für die regioselektive und aromatische Hydroxylierung von p-Xylol entwickelt.…”
unclassified
“…Because the C-F bond dissociation energy is sufficiently high (116 kcal mol À1 ), PFCs are never oxidized by P450BM3 [38]. We assumed that P450BM3 cannot 28], d cyclohexane [28], e ethane and propane [29], f butane [30], g benzene [31], h monosubstituted benzenes [32], i toluene [27], j xylene [33] distinguish between PFCs and fatty acids, because of the similar atomic radius of the fluorine and hydrogen atom. Thus, PFCs would bind to the active site of P450BM3 similarly to the natural substrate-binding manner and initiate activation of molecular oxygen in a similar manner as do long-alkyl-chain fatty acids to afford Compound I ( Fig.…”
Section: Substrate Misrecognition Of P450bm3 For the Hydroxylation Ofmentioning
confidence: 99%
“…The initial rate of phenol formation was reported to be 28 min À1 . A variety of mutants were also constructed for the hydroxylation of substituted benzene substrates such as toluene (R3/I401P mutant with 4 amino acid replacements, R47S, Y51W, A330P, I401P) [27], o-xylene (RLYF/A330P mutant with 3 amino acid replacements, R47S, Y51W, A330P) [33], p-xylene and halogenated benzenes (M2 mutant with 3 amino acid replacements, R47L, Y51F, I401M) [32,35]. These results clearly indicate that mutagenesis of P450s to construct a binding pocket suitable for nonnative substrates is a promising technique.…”
Section: P450bm3mentioning
confidence: 99%